2021
DOI: 10.1098/rsbl.2021.0319
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of human laughter

Abstract: Human adult laughter is characterized by vocal bursts produced predominantly during exhalation, yet apes laugh while exhaling and inhaling. The current study investigated our hypothesis that laughter of human infants changes from laughter similar to that of apes to increasingly resemble that of human adults over early development. We further hypothesized that the more laughter is produced on the exhale, the more positively it is perceived. To test these predictions, novice ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Laughter is not only a signal of joy, pleasure, or amusement, but also a complex social behavior observed among humans and other mammalian species (Kret et al, 2021;Panksepp & Burgdorf, 2003;Provine, 2000;Winkler & Bryant, 2021). Humans laugh as many as 5 times during every 10 min of conversation (Vettin & Todt, 2004), and systematically underestimate the number of times they laugh during the day (e.g., Mannell & McMahon, 1982;Martin & Kuiper, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Laughter is not only a signal of joy, pleasure, or amusement, but also a complex social behavior observed among humans and other mammalian species (Kret et al, 2021;Panksepp & Burgdorf, 2003;Provine, 2000;Winkler & Bryant, 2021). Humans laugh as many as 5 times during every 10 min of conversation (Vettin & Todt, 2004), and systematically underestimate the number of times they laugh during the day (e.g., Mannell & McMahon, 1982;Martin & Kuiper, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…While laughter has received attention from a wide range of researchers-it is present, for instance, in many of Piaget's observations (Piaget, 1945)-systematic studies on laughter development are sparse. There have been studies on laughter phonetics and acoustics in infants (Kret et al, 2021;Sauter et al, 2018) and studies looking at the relationship between child smile and laughter production and several mother characteristics such as personality traits, parenting, and attachment styles (e.g., Bridgett et al, 2013;Malatesta et al, 1989;Washburn et al, 1972). All these studies yield important insights into laughter evolution and the crucial role that laughter has for the development of a baby.…”
Section: Laughter In Mother-child Interaction: Occurrence Duration Ar...mentioning
confidence: 99%
“…More research is, however, needed on this topic. In a recent psychoacoustic study, Kret et al [ 141 ] played back human infant laughter to adult participants, who were asked to determine the airflow direction from the recordings. The researchers found that the infants produced laughter increasingly as an egressive vocalization (i.e.…”
Section: Social Use Of Open-mouth Faces Laughter and Other Play Vocal...mentioning
confidence: 99%
“…The researchers found that the infants produced laughter increasingly as an egressive vocalization (i.e. a vocalization that is produced during the exhalation phase only; see [ 22 , 142 ]) over time and that this acoustic trait was perceived to be more positive by the adult listeners [ 141 ]. Such developmental findings could indicate that human infants already adjust laughter to their acoustic environment via social feedback.…”
Section: Social Use Of Open-mouth Faces Laughter and Other Play Vocal...mentioning
confidence: 99%